2021
DOI: 10.21827/jve.4.37152
|View full text |Cite
|
Sign up to set email alerts
|

Inquiry-based learning and digital storytelling in virtual exchange: an approach for reflecting on food consumption in the Global South and Global North

Abstract: Virtual exchange (VE) in higher education provides an underemployed opportunity for fostering consumer and sustainability competencies. We explore how a crosscultural teaching-learning environment can be designed to encourage students to reflect on a complex global challenge - food consumption patterns - and their role in it. We discuss challenges regarding food consumption as a topic for VE and describe a didactic concept that employs inquiry-based learning and digital storytelling as the framework for studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Predominantly, approaches revolve around the promotion of specific attitudes and/or values. Bartsch et al (2021) assess how consumer and sustainability goals can be developed. Their approach seems to be beneficial for developing consumer and sustainability competences.…”
Section: Evaluation Of Virtual Exchange In Teacher Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Predominantly, approaches revolve around the promotion of specific attitudes and/or values. Bartsch et al (2021) assess how consumer and sustainability goals can be developed. Their approach seems to be beneficial for developing consumer and sustainability competences.…”
Section: Evaluation Of Virtual Exchange In Teacher Educationmentioning
confidence: 99%
“…Furthermore, Viáfara González (2020) observed that STs found it easier to initiate the VE by chatting rather than video calling. In addition, assessment and credits for the workload completed by the students should be considered and should be similar for all participants (Bartsch et al, 2021;Madden, 2022).…”
Section: Overarching Recommendations For Implementing Virtual Exchang...mentioning
confidence: 99%